Hydrogen-rich gas production by the gasification of wet MSW (municipal solid waste) coupled with carbon dioxide capture. (October 2015) - Hu, Mian; Guo, Dabin; Ma, Caifeng; Hu, Zhiquan; Zhang, Beiping; Xiao, Bo; Luo, Siyi; Wang, Jingbo
Abstract: In order to enhance energy recovery efficiency from MSW (municipal solid waste), an in-situ steam gasification method for hydrogen production where CaO was used as CO2 sorbent and catalyst in the process was proposed. The effects of moisture content, the molar ratio of CaO to carbon in wet MSW ([Ca]/[C]) and reactor temperature on H2 yield and gas composition were investigated. The results showed that maximum hydrogen volumetric concentration (49.42 vol%) and hydrogen yield (277.67 ml/g MSW) were obtained at 40 wt.% moisture content at gasification temperature of 750 °C and [Ca]/[C] ratio of 0.7. The proposed direct gasification of wet MSW with in situ CO2 capture process may be a promising route to produce hydrogen rich fuel gas using MSW. Highlights: CaO addition favors municipal solid waste (MSW) gasification at low temperature. Maximum H2 yield and volumetric concentration reached 277.67 ml/g MSW and 49.42 vol%. A process to produce H2 rich gas by MSW gasification with CO2 capture was proposed.